The Application of Graphene Derivatives in Perovskite Solar Cells. Issue 10 (2nd September 2020) - Su, Hongzhen; Wu, Tianhao; Cui, Danyu; Lin, Xuesong; Luo, Xinhui; Wang, Yanbo; Han, Liyuan
Abstract: Perovskite solar cells (PSCs) have attracted much attention due to their high efficiency and low manufacturing cost. However, the defects in perovskite films and the instability issue caused by ion migration limit the further improvement of its efficiency and stability. Graphene and its derivatives are potential materials to solve these problems due to their rich functional groups, environmental stability and compactness, which triggered extensive researches in recent years. In this paper, the development and preparation methods of graphene materials are summarized and then their applications in PSCs are reviewed, with particular emphasis on their function of blocking ion migration. Abstract : In this paper, the development and preparation methods of graphene materials are summarized, and the applications of graphene and its derivatives in perovskite solar cells are reviewed, including defect passivation, ion migration blocking, and charge transport optimization. The progress of graphene as electrode materials in semitransparent and flexible devices is also summarized.